The development of a joyful learning-based Arabic textbook for non-Arabic education study students - Agustien, Resi (INDONESIAN JOURNAL OF SUSTAINABILITY, 2022)
This study aims to design and develop a joyful learning-based Arabic textbook for non-Arabic education study students to find out students’ responses towards the design of the textbook. This study is motivated by various input of students in Ilmu Tarbiyah dan Keguruan Faculty of Institut Agama Islam Bakti Negara (IBN), Tegal. This becomes their hardship in following Arabic lectures especially for the graduate of public schools such as high school and vocational school. The method used in this study is Research and Development method with Borg and Gall development model. The population of this study is the entire students of FITK IBN Tegal of 2020/2021-year academic with 31 samples of the student. The sampling technique of this study uses the probability sampling technique by giving the same opportunity for every population element (member) to be selected as a sample member. The research approach uses a descriptive quantitative approach. A questionnaire is used as a data collecting instrument. The questionnaire is used to collect quantitative data. The result of this study explains that the design expert gives score percentage to textbook design on the material aspect as big as 92% (excellent), learning aspect 97% (excellent), display aspect 91% (excellent), and presentation aspect 94% (excellent). Students’ response to the joyful learning-based Arabic textbook for non-Arabic education study students is excellent with a score percentage as big as 83%.